1994
DOI: 10.1016/0928-8244(94)90068-x
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-independent protection in mice against type Ia group B streptococcus lethal infection

Abstract: There is ample evidence that protection against group B streptococcal (GBS) disease, both in experimental animals and in humans, is related to the presence of specific antibodies and complement. However, until now the possibility of increasing resistance to GBS infection by potentiating natural cell-mediated immunity in the host, has not been explored. In this study we examine the effect of administering in vivo MVE-2 (a polymer fraction of 1,2-co-polymer of divinyl ether and maleic anhydride) and inactivated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1998
1998
1999
1999

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…In fact, a more rapid reduction in the number of intracellular GBS‐Ia and GBS‐III was observed in macrophages activated with IFN‐γ and LPS. This observation seems to be consistent with our previous in vivo data which demonstrated that immunostimulated mice were able to resist a lethal challenge with GBS‐Ia 54 . The effect of macrophage activation on GBS intracellular survival is very interesting if we consider that the phagocytic cells of neonates and preterm babies frequently have a reduced microbicidal activity 15 , 16 , 55 –57 and are therefore more susceptible to GBS infection 58…”
Section: Discussionsupporting
confidence: 90%
“…In fact, a more rapid reduction in the number of intracellular GBS‐Ia and GBS‐III was observed in macrophages activated with IFN‐γ and LPS. This observation seems to be consistent with our previous in vivo data which demonstrated that immunostimulated mice were able to resist a lethal challenge with GBS‐Ia 54 . The effect of macrophage activation on GBS intracellular survival is very interesting if we consider that the phagocytic cells of neonates and preterm babies frequently have a reduced microbicidal activity 15 , 16 , 55 –57 and are therefore more susceptible to GBS infection 58…”
Section: Discussionsupporting
confidence: 90%
“…[22][23][24][25][26] On the other hand, MVE-2 exhibits very few toxic side effects in the treated organisms. Moreover, it has also been utilized in bioconjugates, e.g.…”
Section: Discussionmentioning
confidence: 99%